2007
DOI: 10.1158/1078-0432.ccr-07-0454
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Protein Kinase Cβ by Enzastaurin Enhances Radiation Cytotoxicity in Pancreatic Cancer

Abstract: Purpose: Aberrant activation of protein kinase Ch (PKCh) by pancreatic cancer cells facilitates angiogenesis and tumor cell survival. Targeting PKCh with enzastaurin, a well-tolerated drug in clinical trials, would be expected to radiosensitize pancreatic tumors through direct antitumor and antivascular effects. Experimental Design: We tested the hypothesis that enzastaurin radiosensitizes pancreatic cancer cells in culture and in vivo through inhibition of PKCh. We analyzed pancreatic cancer xenografts for gr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…These indicate that the radiosensitizing effect of enzastaurin on HNSCC cells may be carried out through inhibition of the expression of radioresistance-associated oncoproteins, thereby sensitizing the cells to radiation and resulting in cell death. Consistent with our observation, Spalding et al 19 found that enzastaurin in combination with 2 Gy of radiation can significantly inhibit both GSK3b and PKC b phosphorylation very shortly after adding enzastaurin in pancreatic cancer cell lines BxPC3 and Panc1 and xenograft.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These indicate that the radiosensitizing effect of enzastaurin on HNSCC cells may be carried out through inhibition of the expression of radioresistance-associated oncoproteins, thereby sensitizing the cells to radiation and resulting in cell death. Consistent with our observation, Spalding et al 19 found that enzastaurin in combination with 2 Gy of radiation can significantly inhibit both GSK3b and PKC b phosphorylation very shortly after adding enzastaurin in pancreatic cancer cell lines BxPC3 and Panc1 and xenograft.…”
Section: Discussionsupporting
confidence: 93%
“…It has been found that enzastaurin can dramatically suppress the growth of new vasculature in the rat corneal micropocket 20 and results in decreased microvessel in the Panc1 pancreatic cell line. 19 To investigate the antivascular effects of enzastaurin, we stained mice tumor tissue for CD31 to determine its effect on blood vessel density of each treatment group. We found that enzastaurin alone and enzastaurin in combination with radiation both resulted in decreased blood vessel density compared with no-treatment control, and the combination treatment was most effective at inhibiting blood vessel formation and also induced tumor tissue necrosis; whereas radiation alone was not obviously different from control except for more fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with the PKC inhibitor enzastaurin reduces cancer growth, phosphorylation of GSK3 , and microvessel density in pancreatic cancer-bearing mice when combined with radiation therapy, but enzastaurin alone failed to affect cell survival, proliferation, or xenograft growth [413,414]. On the other hand, in a study using the pancreatic endocrine cancer cell line DON1, enzastaurin (5 and 10 M) increased caspasemediated apoptosis, reduced phosphorylation of GSK3 and Akt, and blocked cell proliferation through the inhibition of insulin-like growth factor-1 (IGF-1) [415].…”
Section: Ovarianmentioning
confidence: 98%
“…Enzastaurin was originally evaluated in human tumour xenograft-bearing mice for its antiangiogenic activity upon PKCb inhibition, as it showed reduction of plasma VEGF levels together with a significant decrease in intratumoural vessel density (Keyes et al, 2004). However, several studies have shown that enzastaurin exhibits direct growth inhibiting effects on a wide array of cultured human tumour cells (Graff et al, 2005;Oberschmidt et al, 2005;Querfeld et al, 2006;Rizvi et al, 2006;Podar et al, 2007;Spalding et al, 2007;Lee et al, 2008). Recent studies suggest that the antitumour effects of enzastaurin are mediated through interference with the phosphatidylinositol 3-kinase (PI3K)/Akt pathway (Graff et al, 2005;Querfeld et al, 2006;Rizvi et al, 2006;Lee et al, 2008), an important pathway regulating the apoptotic response.…”
mentioning
confidence: 99%